1983
DOI: 10.1126/science.6612338
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System Activity Distinguishes Among Emotions

Abstract: Emotion-specific activity in the autonomic nervous system was generated by constructing facial prototypes of emotion muscle by muscle and by reliving past emotional experiences. The autonomic activity produced distinguished not only between positive and negative emotions, but also among negative emotions. This finding challenges emotion theories that have proposed autonomic activity to be undifferentiated or that have failed to address the implications of autonomic differentiation in emotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

44
1,206
6
42

Year Published

1985
1985
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,289 publications
(1,298 citation statements)
references
References 10 publications
44
1,206
6
42
Order By: Relevance
“…Ekman, Levenson, and Friesen (1983) showed that manipulated facial expressions typical of each of six different emotions led to distinctive changes in heart rate and finger temperature. The previously mentioned study conducted by Keltner et al (1993) testifies to the cognitive effects.…”
Section: Effects Of Anger-related Muscular Movementsmentioning
confidence: 99%
“…Ekman, Levenson, and Friesen (1983) showed that manipulated facial expressions typical of each of six different emotions led to distinctive changes in heart rate and finger temperature. The previously mentioned study conducted by Keltner et al (1993) testifies to the cognitive effects.…”
Section: Effects Of Anger-related Muscular Movementsmentioning
confidence: 99%
“…This indicates that BTA in the forehead has positive mood effects above and beyond the euphoria that one gets from improved appearance. The mood-lifting effect of such a BTA treatment may be explained by the facial feedback hypothesis, which dates back to Charles Darwin and William James in the 19th century and has been substantiated in several experimental studies [12][13][14]. In theory, contraction of facial muscles sends a message to the emotional centers of the brain.…”
mentioning
confidence: 94%
“…Importantly, we showed that even when the participant’s attention was directed away from the painful aspect of images depicting another person’s pain, the AIC was still more activated for painful compared to neutral stimuli, while the anterior cingulate cortex showed comparable activations for painful and neutral stimuli (Gu, et al, 2010). Moreover, accumulating evidence suggests that autonomic signals and their higher-order re-representations are crucial for emotional feelings (Craig, 2002; Critchley and Harrison, 2013; Ekman, et al, 1983; Gray and Critchley, 2007; Harrison, et al, 2010; Rainville, et al, 2006). …”
Section: Introductionmentioning
confidence: 99%